China and "La questione criminale" ("the criminal question"): Revolutionary and reformist periods - Cao, Liqun (International journal of law, crime and justice, 2018)
While there is good recent scholarship on the social production of police and crime statistics in China, arguably the matter of the more contextualising "criminal question," particularly during Mao's time (1949-1976), has not been re-visited or scrutinised in recent years. The mixing of revolutionary socialist and post-reform discourses has permitted usages of terms according to their surface meanings in English without consideration of their complex historical meanings. Thus Chinese realities can be misunderstood. In the revolutionary period, crime became broadly conflated with China's own version of Marxist-Leninist law and justice. This article examines the changing nature of the "criminal question" during both Mao's time, where the political question of friend/enemy was key, and the economic reformist period where the social dynamic was based on profit and loss and where the myth of markets and commodities came to be "naturalised."